A scaffold protein connects type IV pili with the Chp chemosensory system to mediate activation of virulence signaling in Pseudomonas aeruginosa. Issue 4 (27th May 2016) - Inclan, Yuki F.; Persat, Alexandre; Greninger, Alexander; Von Dollen, John; Johnson, Jeffery; Krogan, Nevan; Gitai, Zemer; Engel, Joanne N.
Summary: Type IV pili (TFP) function as mechanosensors to trigger acute virulence programs in Pseudomonas aeruginosa . On surface contact, TFP retraction activates the Chp chemosensory system phosphorelay to upregulate 3′, 5′‐cyclic monophosphate (cAMP) production and transcription of virulence‐associated genes. To dissect the specific interactions mediating the mechanochemical relay, we used affinity purification/mass spectrometry, directed co‐immunoprecipitations in P. aeruginosa, single cell analysis of contact‐dependent transcriptional reporters, subcellular localization and bacterial two hybrid assays. We demonstrate that FimL, a Chp chemosensory system accessory protein of unknown function, directly links the integral component of the TFP structural complex FimV, a peptidoglycan binding protein, with one of the Chp system output response regulators PilG. FimL and PilG colocalize at cell poles in a FimV‐dependent manner. While PilG phosphorylation is required for TFP function and mechanochemical signaling, it is not required for polar localization or binding to FimL. Phylogenetic analysis reveals other bacterial species simultaneously encode TFP, the Chp system, FimL, FimV and adenylate cyclase homologs, suggesting that surface sensing may be widespread among TFP‐expressing bacteria. We propose that FimL acts as a scaffold enabling spatial colocalization of TFP and Chp system components to coordinate signaling leading to cAMP‐dependent upregulation of virulence genes on surface contact. Abstract : Type IV pili (TFP) function as mechanosensors to trigger acute virulence programs in Pseudomonas aeruginosa by signaling through the Chp chemosensory system. We show that FimL, a Chp chemosensory system accessory protein of unknown function, acts as a scaffold to enable spatial colocalization of TFP and Chp system components to coordinate cAMP‐dependent transcription of virulence genes upon surface contact. These components are found in other TFP‐expressing bacteria, suggesting that mechanochemical surface sensing may be widespread.